Improving the Yield and some Agronomic Characteristics of Soybean under Water Stress Conditions using Mycorrhiza and Zinc Sulfate - Pouya Sohrabi nour; mohammad ali Abitalebiyan; Javad Hamzei (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
In order to investigate the effect of mycorrhiza inoculation and application method of zinc sulfate fertilizer on yield and some agronomic characteristics of soybean, an experiment was conducted under water stress conditions. This factorial experiment was performed based on a randomized complete block design with three replications in the research farm of Bu-Ali Sina University. Experimental factors were water stress at three irrigation levels after 60, 90 and 120 mm evaporation from the class A evaporation pan; application method of zinc sulfate fertilizer with three levels of foliar feeding, soil application and no-fertilizer and mycorrhiza (Glomus mosseae) in two levels of application and non-application. The results showed that foliar feeding of zinc sulfate in all treatments except severe moisture stress and no-mycorrhiza conditions better than soil application of zinc sulfate led to a significant increase in the number of pods per plant, 100-seed weight, grain yield and zinc concentration. Mycorrhiza increased the number of seeds per pod by 19.5%, harvest index by 17% and seed oil by 5.1%. In the absence of mycorrhiza, there was no difference in grain yield between soil application and non-consumption of zinc sulfate. Moderate moisture stress compared to non-stress conditions increased the grain protein percentage and the highest value (41%) was obtained under moderate moisture stress conditions and mycorrhiza and zinc sulfate foliar feeding. The highest concentration of grain zinc (33.8 mg.kg-1) was obtained from non-stress moisture treatment under the conditions of mycorrhiza and foliar feeding of zinc sulfate In general, yield, oil and protein percentages and zinc content of soybean can be improved by the simultaneous application of mycorrhiza and zinc sulfate foliar application, especially under conditions of moisture stress.